Design of experiments : a no-name approach / Thomas J. Lorenzen, Virgil L. Anderson. - Lorenzen, Thomas J., 1952-; Anderson, Virgil L. (Virgil Lee), 1922- (Statistics, textbooks and monographs ;, 2018)
This volume presents a novel approach to the statistical design of experiments, offering a simple way to specify and evaluate all possible designs without restrictions to classes of named designs. It also presents a scientific design method from the recognition stage to implementation and summarisation.